Spectrophotometric evaluation of shade reproduction of pressable all-ceramic system on un-stained and stained tooth: An in vitro study - Neelam Pande; Maithili S Kolarkar (Wolters Kluwer Medknow Publications, 2016)
Purpose: To evaluate the shade reproduction of a pressable all-ceramic system placed on unstained and stained extracted maxillary central incisor using a color measurement spectrophotometer. In addition, to compare shade reproduction of this material with low translucency and medium opacity on unstained tooth and medium and high opacity on stained tooth. Materials and Methods: Total 45 discs, with difference in the opacity of core, were used. After spectrophotometric evaluation, shade reproduction of the discs was compared and calculated by formula: Δ E+ = ([Δ L+]2+ [Δ a+]2+ [Δ b+]2) 1/2. Results: Student's t-test showed that in a sample of 15, the values of Δ E+ for Group I - LT (Us.T.) lie between 0 and l, for Group II - MO (for Us. as well as S.T.) between l and 2, for Group III - HO (S.T.) are all above 5. Comparison among groups after t-test showed that mean Δ E+ values of Group I - LT is less than Group II - MO for the unstained tooth, Δ E+ for Group II - MO is less than average Δ E+ value of Group III - HO for stained tooth. Conclusion: All-ceramic with low translucency can be used for the fabrication of restoration on the unstained tooth as it gives the best shade reproduction. The medium opacity material may be used on the unstained as well as on stained tooth. However, the clinical implication of high opacity is limited when applied over the stained tooth as it is giving a shade reproduction, which is not within acceptable limits.